A short history of Western ideology a critical account - Petri, Rolf (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2018)
"We are arguably living in a 'postideological' era. However, when we tune into the TV news we can hear political leaders talk about 'advanced' societies, geopolitical experts suggest 'humanitarian' interventions, and sober events presenters qualify a murder as 'barbaric'. What does this mean? In this comprehensive book, Rolf Petri reveals how our everyday political language is full of ideological representations of the world, and places them in an accessible historical narration. From the secularization of Europe and the Enlightenment project of 'civilization' to the contemporary preoccupation with ecological catastrophes or the end of history, A Short History of Western Ideology carves out the central elements of western ideology. It focuses on a wide variety of issues including religion, colonialism, race and gender, which are essential for how we conceive of the modern world. By creating an awareness of the ideological character of the western worldview, its limits and its flaws, this book warns us of the dangers that derive from a self-righteous mindset. It is stimulating and important reading for history and politics students seeking to understand the ideology of the western world"--Provided by publisher.